The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/bdi.12877
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal course and risk factors associated with psychosis in bipolar youths

Abstract: Objectives To compare the longitudinal clinical course of youths with bipolar disorder (BD) spectrum with lifetime (past, intake, and/or follow‐up) psychosis (BDP+) to youths with BD without lifetime psychosis (BDP−). Also, to identify risk factors associated with increased risk of first onset of psychosis during prospective follow‐up. Method Bipolar disorder youths (BDP+ = 137, BDP− = 233), aged 7‐17 years old, were followed on average every 7 months for 11.7 years and were evaluated using standardized instru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 50 publications
(109 reference statements)
0
8
0
Order By: Relevance
“… 83 Further support for the effect of CT during development on functional outcome in adults with first-episode psychosis and BD has been presented by several studies. 84 , 85 Specifically, physical and sexual abuse has a devastating long-term effect, in addition to short-term consequences of greater severity of subclinical symptoms. 85 In contrast, another study in adults with BD did not find a significant relationship between sexual trauma and either of the used chronicity measures of duration of illness or severity of symptoms.…”
Section: Childhood Trauma and Development Of Bipolar Disordermentioning
confidence: 99%
See 1 more Smart Citation
“… 83 Further support for the effect of CT during development on functional outcome in adults with first-episode psychosis and BD has been presented by several studies. 84 , 85 Specifically, physical and sexual abuse has a devastating long-term effect, in addition to short-term consequences of greater severity of subclinical symptoms. 85 In contrast, another study in adults with BD did not find a significant relationship between sexual trauma and either of the used chronicity measures of duration of illness or severity of symptoms.…”
Section: Childhood Trauma and Development Of Bipolar Disordermentioning
confidence: 99%
“… 84 , 85 Specifically, physical and sexual abuse has a devastating long-term effect, in addition to short-term consequences of greater severity of subclinical symptoms. 85 In contrast, another study in adults with BD did not find a significant relationship between sexual trauma and either of the used chronicity measures of duration of illness or severity of symptoms. 86 However, the authors showed an increased probability of poor long-term outcome based on childhood family problems, which encompassed family history of mood disorder.…”
Section: Childhood Trauma and Development Of Bipolar Disordermentioning
confidence: 99%
“…Early age at onset was found to predict a more severe course of illness [ 13 , 27 , 31 , 38 , 54 ]. Other negative prognostic predictors were family history of BD or substance abuse, sexual abuse, suicidality, more severe mood symptoms, and presence of psychotic symptoms [ 14 , 38 , 46 ]. Rates of psychosis of 40% and 61% were reported [ 28 , 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…Rates of psychosis of 40% and 61% were reported [ 28 , 53 ]. Psychosis was associated with a more severe symptomatic course and higher rates of suicide attempt and hospitalization [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation